2011
DOI: 10.1038/npp.2011.93
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activity by Polymorphic Variants of a Remote Enhancer that Supports Galanin Expression in the Hypothalamus and Amygdala: Implications for Obesity, Depression and Alcoholism

Abstract: The expression of the galanin gene (GAL) in the paraventricular nucleus (PVN) and in the amygdala of higher vertebrates suggests the requirement for highly conserved, but unidentified, regulatory sequences that are critical to allow the galanin gene to control alcohol and fat intake and modulate mood. We used comparative genomics to identify a highly conserved sequence that lay 42 kb 5' of the human GAL transcriptional start site that we called GAL5.1. GAL5.1 activated promoter activity in neurones of the PVN,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(93 citation statements)
references
References 72 publications
(83 reference statements)
1
92
0
Order By: Relevance
“…Magnetofection has been also used for effective gene transfer in cultures of multipotent rat neural precursor cells and rat oligodendrocyte precursors [21,22]. In primary cultures of rat hypothalamic neurons, magnetofection was used to transfect the CG and CA alleles of an enhancer sequence related to galanin expression [23]. Magnetofection in mouse embryonic motor neurons was used to transfect a plasmid encoding the gene for a fluorescent protein fused to the spinal muscular atrophy-disease protein Smn.…”
Section: Neuronal and Glial Cellsmentioning
confidence: 99%
“…Magnetofection has been also used for effective gene transfer in cultures of multipotent rat neural precursor cells and rat oligodendrocyte precursors [21,22]. In primary cultures of rat hypothalamic neurons, magnetofection was used to transfect the CG and CA alleles of an enhancer sequence related to galanin expression [23]. Magnetofection in mouse embryonic motor neurons was used to transfect a plasmid encoding the gene for a fluorescent protein fused to the spinal muscular atrophy-disease protein Smn.…”
Section: Neuronal and Glial Cellsmentioning
confidence: 99%
“…3. The GAL gene is widely expressed in the human brain [e.g., LC, forebrain, amygdala, and hypothalamus (26,51)], but its involvement in the development of depression is not well understood. Although previous studies indicated that it might have a sex-or estrogen-dependent effect (49), in our study the galanin system genetic variants significantly influenced the depressionrelated phenotypes both in males and in females, with similar magnitude of effect size, providing evidence that the excessive stress effect is not mediated by sex.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent functional studies provided the first evidence that polymorphisms in a highly conserved genetic region upstream from the GAL gene regulates GAL expression in brain areas, such as the amygdala and hypothalamus, implicated in the pathogenesis of depression (51,52).…”
mentioning
confidence: 99%
“…Thus, galanin interacts with 5-HT1A receptors, and galanin antagonists and agonists have anxiolytic and antidepressive effects in animal experiments (144)(145)(146)(147)(148)(149)(150)(151). Interestingly, association of genes encoding galanin and/or GalR3 has been reported for psychiatric phenotypes (152)(153)(154), including panic disorder (155), depression-related parameters (156)(157)(158), and nicotine dependence (159,160).…”
Section: Significancementioning
confidence: 99%